Non‐vitamin K antagonist oral anticoagulants in cardiovascular disease management: evidence and unanswered questions. (3rd January 2014) - Cheng, J. W.; Barillari, G.
Summary What is known and objective Anticoagulation is important in the management of cardiovascular disorders; however, traditional anticoagulants such as heparins and vitamin K antagonists (VKAs) have limitations, including parenteral administration with the former and the need for coagulation monitoring and dose adjustments with the latter. Three non‐VKA oral anticoagulants (OACs), dabigatran, rivaroxaban and apixaban, are available for the prevention of stroke in patients with atrial fibrillation (AF) and may change clinical practice. This article reviews current knowledge and important unanswered questions on the use of these agents in patients with cardiovascular disease. Methods A literature search was performed using PubMed and the search terms dabigatran, rivaroxaban, apixaban, AF and acute coronary syndrome (ACS). Peer‐reviewed, published clinical trials, review articles, relevant treatment guidelines and prescribing information documents were identified and reviewed for relevance. Results and discussion Dabigatran is an oral direct thrombin inhibitor; rivaroxaban and apixaban are oral direct Factor Xa inhibitors. These agents have a quicker onset and offset of action, more predictable pharmacokinetic and pharmacodynamic profiles, and fewer drug–drug interactions than VKAs, allowing use of fixed doses. For the prevention of stroke in patients with AF, the non‐VKA OACs were either non‐inferior or superior to warfarin with similar or improved bleeding profiles, particularly with respect to reductions in intracranial haemorrhage. In patients with ACS receiving dual antiplatelet therapy, the addition of rivaroxaban significantly reduced the rate of death from cardiovascular causes, myocardial infarction or stroke without increasing fatal bleeding, but led to higher rates of major bleeding. Dose reductions with non‐VKA OACs are mandated in certain circumstances in patients with AF, such as moderate renal impairment. Contraindications include creatinine clearance <15 mL/min (<30 mL/min for dabigatran in Europe and Canada) and moderate or severe hepatic impairment, but patients can be transitioned to other anticoagulants if appropriate. It is unknown which non‐VKA OAC is optimal for stroke prevention in patients with AF, although factors such as co‐medications (e.g. dabigatran may be preferred if a patient is taking a co‐medication that is a strong cytochrome P450 3A4 inhibitor) and renal function (rivaroxaban and apixaban depend less on renal clearance than dabigatran) will be important for individual patients. Addition of rivaroxaban to antiplatelet therapy for prevention of recurrent events in patients with recent ACS is approved in Europe for patients at the highest risk (with elevated cardiac biomarkers) and must take into account the increased risk of major bleeding. Although routine coagulation monitoring is not required, an understanding of which assays are appropriate for each non‐VKA OAC and how they are affected is important. In a bleeding emergency, non‐specific prohaemostatic agents are suggested to reverse the action of the non‐VKA OACs, but more clinical data are needed. What is new and conclusion Non‐VKA OACs provide similar or improved efficacy and, on current evidence, improved safety. They provide greater convenience, compared with traditional anticoagulants for the prevention of stroke in patients with AF. Rivaroxaban may be of benefit to selected high‐risk patients with ACS. Selection of the most appropriate non‐VKA OAC will depend on individual patient factors.